TE'MOANE COMMUNITY PARTICIPATION IN DEVELOPING ISLAMIC RELIGIOUS EDUCATION AT MADRASA ALIAYAH AL-MUNAWARAH - Widiastuti, Ria; Basri; Rahim, Abdul (JEC (Jurnal Edukasi Cendekia), 2024)
This research is a qualitative research with the research population being the people of Te'moane Village, Tomia District, Wakatobi Regency. As a qualitative research, the instruments used are also qualitative instruments, observation, interviews and. Therefore, in collecting data using qualitative instruments as above using observation, interviews and documentation to determine the condition of the research object in addition to that in qualitative data analysis including: editing, categorization, tabulation and interpretation. The results of this study indicate that: 1) The participation of the Te'moane community in developing Islamic education at the Al-Munawarah Tomia Islamic Senior High School is by forming Aqidah, Morals of Muammalah, then involving children in religious studies or TPQ, then always helping when there are school renovation activities, the community always helps in the form of manpower, 2) Obstacles in developing Islamic education at the Al-Munawarah Tomia Islamic Senior High School are as follows. The first is the limited number of Islamic religious education teachers, the second is the availability of inadequate facilities and infrastructure and the third is from the students themselves who have very minimal knowledge about Islamic education because they were not provided with informal education before.